Lobbist Organizations as Conflict Resolution Institute - Olegovna Molchanova, Alyona; Valer’evna Khramova, Evgeniya (International Journal of Criminology and Sociology, 2022)
The study specified in this article is devoted to an important problem in the modern state management practice of Russia - the study of conflict resolution of such a politically significant institute as lobbist organizations. The authors consider the phenomenon from a socio-economic, organizational, political perspective, which is categorized through the conceptual series “government relations - public administration - political institute” and is scientifically justified. The analysis methodology is based on the symbiosis of the neoinstitutional approach and game theory (continuous games) with the rent-oriented behavior of players. The urgency of the problems of lobbist organizations is due to the prolonged political and managerial crisis, both in Europe, the USA and in the countries of Asia. The scientific novelty of this paper is determined by the use of the neoinstitutional approach and the theory of games with the rent-oriented behavior of players as the fundamental methodological direction of the symbiosis when considering lobbist organizations as conflict resolution institutes with all the functions and rules of behavior in a political game inherent in them. The study will be based on the use of such empirical methods as analysis of documents and cases, which justifies the use of a qualitative methodology. The article is one of the first in Russian empirical practice related to the problem of lobbist organizations and, undoubtedly, will make a significant contribution to the study of the conflict logical specific nature of this socio-political institute. The article is part of the grant of the Russian Foundation for Basic Research No. 19-011-31376opn “Conflict logical audit as a system of technologies for influencing ideological youth extremism in modern Russia”.